Broad-Spectrum Antibiotic Treatment and Subsequent Childhood Type 1 Diabetes: A Nationwide Danish Cohort Study - Clausen, Tine D.; Bergholt, Thomas; Bouaziz, Olivier; Arpi, Magnus; Eriksson, Frank; Rasmussen, Steen; Keiding, Niels; Løkkegaard, Ellen C. (PloS one, 2016)
Studies link antibiotic treatment and delivery by cesarean section with increased risk of chronic diseases through changes of the gut-microbiota. We aimed to evaluate the association of broad-spectrum antibiotic treatment during the first two years of life with subsequent onset of childhood type 1 diabetes and the potential effect-modification by mode of delivery. A Danish nationwide cohort study including all singletons born during 1997-2010. End of follow-up by December 2012. Four national registers provided information on antibiotic redemptions, outcome and confounders. Redemptions of antibiotic prescriptions during the first two years of life was classified into narrow-spectrum or broad-spectrum antibiotics. Children were followed from age two to fourteen, both inclusive. The risk of type 1 diabetes with onset before the age of 15 years was assessed by Cox regression. A total of 858,201 singletons contributed 5,906,069 person-years, during which 1,503 children developed type 1 diabetes. Redemption of broad-spectrum antibiotics during the first two years of life was associated with an increased rate of type 1 diabetes during the following 13 years of life (HR 1.13; 95% CI 1.02 to 1.25), however, the rate was modified by mode of delivery. Broad-spectrum antibiotics were associated with an increased rate of type 1 diabetes in children delivered by either intrapartum cesarean section (HR 1.70; 95% CI 1.15 to 2.51) or prelabor cesarean section (HR 1.63; 95% CI 1.11 to 2.39), but not in vaginally delivered children. Number needed to harm was 433 and 562, respectively. The association with broad-spectrum antibiotics was not modified by parity, genetic predisposition or maternal redemption of antibiotics during pregnancy or lactation. Redemption of broad-spectrum antibiotics during infancy is associated with an increased risk of childhood type 1 diabetes in children delivered by cesarean section.